2011
DOI: 10.1007/s11999-010-1695-8
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Notching in Reverse Shoulder Arthroplasty: Is It Important to Avoid It and How?

Abstract: Level IV, Therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(164 citation statements)
references
References 14 publications
9
151
1
3
Order By: Relevance
“…In our series, patients who had a better pre-operative ROM and therefore a greater post-operative ROM were more at risk for developing a scapular notch [30]. This was also true for patients with a BMI <30, which is in agreement with previous studies [14,29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our series, patients who had a better pre-operative ROM and therefore a greater post-operative ROM were more at risk for developing a scapular notch [30]. This was also true for patients with a BMI <30, which is in agreement with previous studies [14,29].…”
Section: Discussionsupporting
confidence: 92%
“…Except for a lower risk of notching in obese patients, BMI did not influence the rate of complications in our series as opposed to results reported by Gupta et al [21]. However, as opposed to reports in previous publications [30,38,40], we found no influence of scapular notching on postoperative active ROM or on complication rates; however, as with Favard et al [15], our results confirmed the deleterious effect of superior tilt.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, SN did not influence the clinical or the radiological outcome. This concurs with the findings of Lévigne et al [10]. On the other hand, Simovitch et al [8] found that SN resulted in poorer outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The distance between the two lines was calculated and values more than 0 mm were regarded as overhang. Glenoid baseplate inclination was described as the angle between the baseplate and a horizontal line drawn from the upper margin of the glenoid as recommended by Lévigne et al [10] (Fig. 1c).…”
Section: Methodsmentioning
confidence: 99%